Bottle Gourd as an Implement for the Poor in Roman Italy - Brittany Bauer (EXARC Journal)
Bottle gourds, which are thought to have originated in Africa, have been collected and cultivated in Italy since antiquity for the making of vessels and utensils, as well as food, musical instruments, and fishing buoys (Janick, Paris and Parish, 2007, p.1441). Columella and Pliny the Elder both write extensively about the uses of bottle gourds, yet the importance of this vegetable in antiquity is notably absent from modern scholarship. The thick skin of the bottle gourd, which may be a trait of domestication, is the reason why the fruit makes such an excellent container (Schlumbaum and Vandorpe 2012, p.500). In order for a household to maintain economic independence, and survive under conditions of crop failure, hardship, and seasonal changes, a well-made storage vessel would have been essential. The functionality and performance of the storage vessel would have determined the longevity of the products inside, and thus directly contributed to the well-being of the user (Villing and Spataro 2015, p.9). Ceramics, the most noted type of vessel used in antiquity, required skill, time, and special equipment to make, and therefore would not have been practical for all poor people to produce or buy. If a poor family grew a crop of bottle gourds, however, not only would they get food from it, but a few gourds left on the vine to harden could easily be transformed into storage vessels, bowls, portable water containers, or utensils. This project is intended to explore the underrepresented aspects of poor culture, using both textual and archaeological information.